2011
DOI: 10.1093/jxb/err341
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variants of the amylose extender mutation of maize demonstrate phenotypic variation in starch structure resulting from modified protein-protein interactions

Abstract: amylose extender (ae−) starches characteristically have modified starch granule morphology resulting from amylopectin with reduced branch frequency and longer glucan chains in clusters, caused by the loss of activity of the major starch branching enzyme (SBE), which in maize endosperm is SBEIIb. A recent study with ae− maize lacking the SBEIIb protein (termed ae1.1 herein) showed that novel protein–protein interactions between enzymes of starch biosynthesis in the amyloplast could explain the starch phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(140 citation statements)
references
References 71 publications
6
133
0
1
Order By: Relevance
“…2; Supplemental Fig. S1) through a decrease in the number of available nonreducing termini of glucan chains available for SSs (Liu et al, 2012a). Further dynamic expression analysis of the three SBEs indicated that the SBEs were inhibited gradually along with endosperm development in TRS, while in TQ, it showed an increased protein level until 10 DAF but then a decreasing trend ( Fig.…”
Section: Pleiotropic Effects Of Sbei and Sbeiib Down-regulation On Otmentioning
confidence: 93%
“…2; Supplemental Fig. S1) through a decrease in the number of available nonreducing termini of glucan chains available for SSs (Liu et al, 2012a). Further dynamic expression analysis of the three SBEs indicated that the SBEs were inhibited gradually along with endosperm development in TRS, while in TQ, it showed an increased protein level until 10 DAF but then a decreasing trend ( Fig.…”
Section: Pleiotropic Effects Of Sbei and Sbeiib Down-regulation On Otmentioning
confidence: 93%
“…The precise mechanism underlying the association of specific enzymes of starch synthesis with the starch granule are not known, although it has been suggested that alternative splicing of SBEII in bean (Phaseolus vulgaris L.) leads to partitioning within the starch granule (27). Recent evidence suggests that granule-associated proteins (including the SBEII class) become entrapped in the granule through association in heteromeric protein complexes (8,53). Distinct roles for SBEI and SBEII classes in amylopectin synthesis were suggested by the analysis of glucans produced when different combinations of maize SSs and SBEs were heterologously expressed in E. coli (54).…”
Section: Tablementioning
confidence: 99%
“…It is notable that both the Ser 649 and Ser 286 motifs are completely absent from SBEI, again suggesting a distinct class of functions for these sites. There is evidence of competition for the different phosphorylation sites by the plastidial CDPKs, as an allelic mutant of amylose extender maize expressing a truncated form of SBEIIb lacking Ser 286 and Ser 297 becomes hyperphosphorylated at the remaining Ser 649 residue (53). Phosphorylation of SBEs plays a critical role in the formation of heteromeric protein complexes with SSs and other SBE isoforms (see below).…”
Section: Regulation Of Sbes By Protein Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The developing endosperms of maize su2 (ΔSSIIa), amylose extender (ae, ΔBEIIb), sbe2a (ΔBEIIa), and dull1 (ΔSSIII) mutants have demonstrated the absence of the high molecular weight (>600 kDa) starch biosynthetic enzyme complexes, suggesting that SSIIa, SBEIIb, SBEIIa and SSIII are essential components for this complex [135]. SBEIIb-deficient maize mutant recruited SBEI, SBEIIa and Pho1 to form the SSI, SSIIa, SBEI, SBEIIa and Pho1 complex instead of SSI, SSIIa and SBEIIb [135], while the maize mutant containing an inactive SBEIIb formed a SSI, SSIIa, SBEI and SBEIIa complex [136]. This difference might result in the difference in starch structure observed from these studies.…”
Section: Enzyme Complexesmentioning
confidence: 99%